Social and philanthropical work in service to early childhood education in the city of Viçosa - MG: Representation of teachers and coordinators (Research, Society and Development, 2023)
The objective was to identify, through a qualitative descriptive methodology, the practice of social entities providing care to children in the Municipality of Viçosa - MG. Initially, we sought to characterize the municipality's social and philanthropic institutions, especially those that work to assist children from the lower classes who live in situations of risk or social vulnerability; in addition to identifying the perspective of employees, including teachers, coordinators and directors; and understand the role played by public authorities in relation to the work carried out by philanthropic entities in the municipality of Viçosa - MG. The themes researched helped to understand that the social problems that currently exist, and which affect poor children, are the same as those of the 12th century. They are, however, interpreted and analyzed differently over the years, which has led to the search for more effective means to combat neglect of childhood through public policies, with a view to their recognition and appreciation.